Resiliensi Orang Tua Sunda yang Memiliki Anak Berkebutuhan Khusus - Nisa Hermawati (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
Having children with special needs require higher patience. This research aims to look specifically how resilience of the Sundanese couple who have child with special needs. They have three factors: have the personal stronger to face all difficulties they need face (I AM), have external support, which are love and care each other (I HAVE), and have good interpersonal relation with their friends or family (I CAN). This description is similar with the meaning of personality in Sundanese, which are “cageur, bageur, bener, singer, pinter and silih asih, silih asah, silih asuh.”